The Future of man proceedings of a Symposium held at the Royal Geographical Society London, on 1 April, 1971. - Ebling, F. J. G. (Francis John Govier), 1918-1992; Heath, G. W. (Gordon William) (Symposia of the Institute of Biology, 1972)
The Future of Man.